Investigating the impact of ‘Postcard Adventure’ in ESL classrooms - Abd Halim, Syakirah (RSIS, 2024)
This qualitative research paper explores the impact of ‘Postcard Adventure’, an online game created to bridge the gap between entertainment and education. The study assesses the effectiveness of ‘Postcard Adventure’ in enhancing language learning outcomes, measuring student engagement, promoting cultural awareness, and evaluating the implications of gamification in language education. Through semi-structured interviews, this research aims to contribute valuable insights into the potential of gamified approaches for language acquisition, particularly in remote learning. The findings shed light on the success of ‘Postcard Adventure’ and offer recommendations for educators seeking innovative methods to impart language skills, especially in challenging circumstances. This research also emphasised the primary motivation behind the development of ‘Postcard Adventure’, which aids busy teachers in producing captivating educational content.